New insulin glargine 300 U/ml versus glargine 100 U/ml in Japanese adults with type 1 diabetes using basal and mealtime insulin: glucose control and hypoglycaemia in a randomized controlled trial (EDITION JP 1) - Munehide Matsuhisa; Masayoshi Koyama; Xi Cheng; Yoshinori Takahashi; Matthew C. Riddle; G. B. Bolli; T. Hirose (2015)
To compare efficacy and safety of new insulin glargine 300 U/ml (Gla-300) with that of insulin glargine 100 U/ml (Gla-100) in Japanese adults with type 1 diabetes.